Thermal regime of annual air temperature in Bosnia and Herzegovina - Drešković, Nusret; Mirić, Ranko (Journal for Geography, 2017)
Horizontal air temperature is defined by the value of the mean air temperature for a certain surface area unit. It is defined by the value of horizontal thermal gradient, i.e. the value of average change of horizontal temperature per unit area. In order to define the horizontal change of air temperature in Bosnia and Herzegovina, a GRID thermal model was constructed whose spatial resolution is 20 m. Based on obtained thermal model geo-database it was determined that the mean annual air temperature for the whole area of Bosnia and Herzegovina is about 10.9 °C, keeping in mind that there are significant thermal differences with respect to the two existing climate zones. More specifically, on the territory of the northern temperate climate zone the average annual temperature is about 9.7 °C, while in the Mediterranean climate zone the said value is 12.1 °C. In this work, it was also found that thermal contrasts are very pronounced as well, due to the fact that average annual temperature in the highest mountain peak zones in southeastern Bosnian highlands is negative and is found to be -1.4 °C (Maglić peak), while at the Neum coastal zone it is measured at 15.9 °C. The above stated pronounced thermal contrasts are determined on a small horizontal distance, as a consequence of climactic position of Bosnia and Herzegovina as well as highly pronounced terrain dynamics.